Baseline assessment of coral and fish assemblage relationships in Tanjung Palas Timur Marine Protected Area, North Kalimantan, Indonesia - ENCIK WELIYADI; SUTRISNO ANGGORO; HAERUDDIN HAERUDDIN; SURADI WIJAYA SAPUTRA; MUHAMMAD NAJIB; FAHYUNI AMALIAH; ARDY ANDREAS BERNARD KASE; MUHAMMAD YUSFI YUSUF; MOHAMMAD FADNAN AKHMADI (Society for Indonesian Biodiversity, 2025)
Abstract. Weliyadi E, Anggoro S, Haeruddin, Saputra SW, Najib M, Amaliah F, Kase AAB, Yusuf MY, Akhmadi MF. 2025. Baseline assessment of coral and fish assemblage relationships in Tanjung Palas Timur Marine Protected Area, North Kalimantan, Indonesia. Biodiversitas 26: 5303-5313. Coral reefs are vital ecosystems supporting biodiversity, coastal defense, and local livelihoods, but remain vulnerable to human and environmental pressures. This study provides the first integrated ecological baseline for the core zone of the Tanjung Palas Timur Marine Protected Area (KKPTPT), North Kalimantan, Indonesia. Using Underwater Photo Transect (UPT) and Underwater Visual Census (UVC) methods alongside key water quality measurements, the study assessed coral cover, reef fish assemblages, and environmental parameters. Multivariate analyses: Jaccard similarity, Principal Coordinate Analysis (PCoA), Mantel test, and Procrustes analysis were employed to explore community patterns. The average live coral cover was moderate (46.19%), with higher values on fringing reefs. Coral species richness peaked at Station 1 (19 species), while fish richness was highest at Station 4 (8 species). Mantel (r: -0.452, p: 0.085) and Procrustes (M²: 0.624, p: 0.33) analyses indicated weak congruence between coral and fish assemblages. Slight increases in TSS were associated with reduced biological richness, while stable hydrodynamic conditions supported reef health. These findings emphasize the importance of sediment management and habitat structure in sustaining reef resilience. These findings suggest that fish diversity is not solely dependent on coral assemblages but also influenced by environmental drivers such as substrate stability and hydrodynamics. The study offers critical insights for ecosystem-based management through sediment control, substrate rehabilitation, adaptive zoning, and participatory monitoring.